Öğretmen Adaylarının Halk Kültürüne Yönelik Algılarının İncelenmesi / An Investigation of Pre-Service Teachers’ Perceptions of Folk Culture - Gürgil, Fitnat (Journal of History Culture and Art Research, 2017)
Abstract The purpose of this study is to determine pre-service teachers’ perceptions of folk culture. The study uses the qualitative research method. The study group consists of pre-service teachers studying in the sports sciences and education faculties of a state university located in Ankara province of Turkey. The research data have been collected through a metaphor form and semi-structured interviews to identify the participants’ perceptions of folk culture. The obtained data have been subjected to content analysis. The analysis results of the metaphor data indicate that the pre-service teachers associate folk culture with ‘inevitable and valuable element’ most, followed by ‘informative/directive elements’. The analysis results of the interview data, on the other hand, point out that the participants largely highlight folk culture’s function as informing about values of society. Another finding of the study is that the pre-service teachers’ perceptions of folk culture considerably differ by their subject branch. Especially the pre-service teachers receiving education in the field of sciences (70%) have negative perceptions towards folk culture. Also, it has been noticed that some of the participating pre-service teachers have misconceptions regarding folk culture. The analyses of the metaphor and interview data have revealed that some pre-service teachers think culture has an unchangeable nature and so opposes development and science. Öz Bu çalışma, öğretmen adaylarının halk kültürüne yönelik algılarının tespit edilmesi amacını taşımaktadır. Nitel araştırma yöntemine göre desenlenen araştırmanın çalışma grubunu, Ankara ilinde bulunan bir devlet üniversitesinin spor bilimleri ile eğitim fakültelerinde öğrenim gören öğretmen adayları oluşturmaktadır. Katılımcıların halk kültürüne ilişkin algılarını tespit etmek amacı ile çalışmada hem metafor formu hem de yarı yapılandırılmış görüşmeler yoluyla veriler toplanmıştır. Elde edilen veriler içerik analizine göre incelenmiştir. Metafor verilerinin analizine göre öğretmen adaylarının halk kültürünü en fazla ‘vazgeçilmez ve değerli unsur’ daha sonra ise ‘bilgilendirici/yönlendirici unsur’ olarak nitelendirdiği tespit edilmiştir. Görüşme verilerinin analizinde ise katılımcıların yoğun olarak halk kültürünün toplumu bilgilendirme işlevine vurgu yaptıkları görülmüştür. Araştırmanın bir başka sonucu ise öğretmen adaylarının halk kültürüne yönelik algılarının öğrenim görülen branşlar açısından derin farklılıklar göstermesidir. Özellikle fen bilimleri alanında öğrenim gören öğretmen adaylarının (%70) halk kültürüne yönelik olumsuz algılara sahip olduğu tespit edilmiştir. Araştırma sonucunda çalışmaya katılan öğretmen adaylarının bir kısmının zihninde halk kültürüne ilişkin kavram yanılgılarının olduğu da görülmüştür. Hem metafor hem de görüşme verilerine göre bazı öğretmen adaylarının zihninde kültürün değişmez yapıda olduğu ve bu yapıdan kaynaklı olarak gelişmenin ve bilimselliğin karşıtı olarak algılandığı bulgusuna ulaşılmıştır.